Disconnection: How Measured Separations From Journalistic Norms and Labor Can Help Sustain Journalism. (February 2022) - Bélair-Gagnon, Valérie; Bossio, Diana; Holton, Avery E.; Molyneux, Logan
This commentary considers the concept of "disconnection" as a way to understand practices of contemporary digital journalism while advocating for consideration of disconnection as a necessary component of sustainable journalism.